Taxonomic review of Hisonotus Eigenmann & Eigenmann (Siluriformes: Loricariidae: Hypoptopomatinae) from the laguna dos Patos system, southern Brazil - Carvalho,Tiago Pinto (2011)
The species of Hisonotus from the laguna dos Patos system are reviewed. Two species with wide distributions are redescribed: Hisonotus laevior and H. nigricauda. Six new species are described from that system: H. notopagos from the rio Camaquã drainage; H. carreiro and H. prata, endemic from the headwaters of rio Taquari drainage; H. vireo, widely distributed in the rio Jacuí basin; and H. brunneus and H. heterogaster restricted to tributaries of the rio Jacuí drainage. Hisonotus leptochilus is here considered a junior synonym of H. laevior. Hisonotus armatus, H. charrua, H. leucofrenatus, and H. taimensis are also present in the region and in total there are twelve species of Hisonotus in the laguna dos Patos system. Their distributions are discussed, species are illustrated and a taxonomic key is provided.